The epidemiology of abnormal hemoglobins in Mediterranean high-level athletes - Touhami, I.; Fattoum, S.; Bibi, A.; Siala, H.; Messaoud, T.; Koubaa, D.; Mankai, R.; Bartagi, Z.; Le Callais, D. (European Journal of Applied Physiology, 2010)
The aim of this study was to determine the prevalence and nature of hemoglobin (Hb) defects in a Mediterranean high-level (HL) athlete population. Five hundred and ninety-four HL male and female athletes were recruited during the annual follow-up of the members of Tunisian national teams. Hematological data, Hb electrophoresis, and DNA analysis were assessed using conventional techniques. Sporting discipline, type of sport, and performance levels were assessed using a questionnaire. The results showed that 32 HL athletes had abnormal Hb (5.4%): ß-thalassemia (2.2%), a-thalassemia (0.5%), HbAS (1.5%), HbAC (0.5%), and rare Hb variants (0.7%). Of the 32 defect carriers, all but one (a a-thalassemia) were heterozygous. All the detected hemoglobinopathies but one (an Hb Hope) had already been reported in the country. The prevalence of Hb defect in the HL athletes was similar to that described in the general Tunisian population (P > 0.05). The percentage of Hb defect in the athletes was not dependent on gender, or performance level (P > 0.05). Within each type of sport the percentages of athletes with normal and abnormal Hb were similar (P > 0.05). The hematological data revealed the diversity of anemia, microcytosis, and hypochromia in thalassemic HL athletes. We concluded that HL athletes in Tunisia were a representative sample of the general Tunisian population regarding the prevalence and nature of benign abnormal Hb. The hematological data of the thalassemia carriers exhibited high variability and raised the question of genetic and sporting counseling, as well as biological follow-up for these carriers.